Answer with Step-by-step explanation:
We know that the components of velocity are obtained from position as
![u=(dx)/(dt)\\\\v=(dy)/(dt)](https://img.qammunity.org/2020/formulas/mathematics/college/jzwtfe98nd6segs93dq4su0lbep0549nub.png)
Using the given values we obtain
![u=(d(2t^2))/(dt)\\\\u=4t](https://img.qammunity.org/2020/formulas/mathematics/college/4jo5bxcn4wrot4hhgfjb60bbu1hjwg8mla.png)
Similarly
![v=(d(t^2-41))/(dt)\\\\u=2t](https://img.qammunity.org/2020/formulas/mathematics/college/7aan9av13t7xassm8tzzrai60riyjgmjft.png)
The the velocity function can be written as
![\overrightarrow{v}=4t\widehat{i}+2t\widehat{j}](https://img.qammunity.org/2020/formulas/mathematics/college/6lv5c4bsyontxhakiv7w7rbslppuszfu53.png)
The components of acceleration are obatined from the components of velocity as
![a_(x)=(du)/(dt)\\\\a_(y)=(dv)/(dt)](https://img.qammunity.org/2020/formulas/mathematics/college/b22wp9muklc7w5mziq1smd6reawovr7ixt.png)
Using the given values we obtain
![a_x=(d(4t))/(dt)\\\\a_(x)=4](https://img.qammunity.org/2020/formulas/mathematics/college/byhg0lzlr6t68i5a2x0xsq0q5252hdg80q.png)
Similarly
![a_y=(d(2t))/(dt)\\\\a_y=2](https://img.qammunity.org/2020/formulas/mathematics/college/3jejpq50fk4ro3xsimiwskrs5i894wsg48.png)
The the acceleration function can be written as
![\overrightarrow{a}=4\widehat{i}+2\widehat{j}](https://img.qammunity.org/2020/formulas/mathematics/college/51feqkrg72bh0sr0y1dohzi3gqeji70v4s.png)
Thus at time 't=1' the velocity function becomes
![\overrightarrow{v}=4\widehat{i}+2\widehat{j}](https://img.qammunity.org/2020/formulas/mathematics/college/qf3lk6etix05jf9ibc7yjwejarttdqcd53.png)
Thus the component of acceleration in the direction of the given vector
can be found by taking the dot product of the 2 vectors
Thus we get
![v_(r)=\overrightarrow{v}\cdot \overrightarrow{r}\\\\v_(r)=(4\widehat{i}+2\widehat{j})\cdot (\widehat{i}-3\widehat{j})\\\\v_(r)=4-6=-2](https://img.qammunity.org/2020/formulas/mathematics/college/d5ytn58xjy6ystfhr28fm3phn3scgnqgy3.png)
Similarly the dot product is obtained for acceleration as
![a_(r)=\overrightarrow{a}\cdot \overrightarrow{r}\\\\a_(r)=(4\widehat{i}+2\widehat{j})\cdot (\widehat{i}-3\widehat{j})\\\\a_(r)=4-6=-2](https://img.qammunity.org/2020/formulas/mathematics/college/6bifjzjylldi5foohcw6xh9criuejg62as.png)